The system of exercises in forming the phonostylistic skills of students in senior grades (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the notion of phonostylistic skills of students in senior grades; the system of exercises for effective forming of the phonostylistic skills is considered by the author.
Keywords: phonostylistic skills; classification of exercises; stylistic editing